Penerapan Pembuatan Media Pembelajaran Dari Bahan Bekas Melalui MGMP Biologi Tingkat SMA Sederajat Kabupaten Aceh Tamiang - Kusnafizal, Teuku; Nursamsu, Nursamsu (Jurnal Pendidikan Biologi, 2017)
Dialogue of teacher in spesific lesson (MGMP) is a forum for develop of environment teacher in specific lesson and as a place to make same perceftion for somethting that has correlation with learning process especially for one lesson. The aim of this activity had been done by tim of PKM in MGMP to make media from used media was given knowledge to the biologyâs teachers in MGMP at the level of senior high school in Aceh Tamiang. The method in this activity was descriptif qualitative. The sample in this activity was 30 participants that consist of teachers through biology MGMP at level of senior high school in Aceh Tamiang. The result of this activity from the questoner was share for biologyâs teachers and got the result 75% that answered âAgreeâ to continue this activity used in learning process. So, it can conclude that this activity got good respond to continue the knowledge in learning process at school.